Technical and tactical performance indicators based on the outcome of the set in the school volleyball - Costa, Yago Pessoa da (2017)
The aim of the study was to identify and compare the technical and tactical performance indicators based on the outcome of the set in the school female volleyball. The study included 110 athletes, aged between 12 and 14 years, belonging to 11 teams. Fifty-eight sets of 28 games were filmed and 7194 actions, 2830 serves, 2157 serve reception, 1358 passes and 1299 attacks were analyzed. Afterwards, the game sets were divided into winners and losers sets. Teams that won the sets had advantage at the serve reception, set and attack on error and excellence/point criteria (p< 0.05) and of serve, set and attack (p< 0.001). In conclusion, the winner’s sets were those with a better technical-tactical performance quantitatively and qualitatively.